Enhancing Audit Quality: Key Factors and the Role of Rewards in Government Internal Audits at the Financial Audit Agency of North Sumatra - ., Nazarwin; Manik, Yuni Mariani; Sudirman, Amalia Nurannisa; Lubis, Indah Sari (Journal of Ecohumanism, 2025)
Numerous audit findings identified by the BPK, rather than the inspectorate—tasked with serving as an internal auditor and an early warning system—indicate that the quality of government internal audits remains inadequate. This observation suggests that the internal audit processes within government institutions have yet to achieve an optimal standard. The principal aim of this study is to analyze the influence of internal supervision, audit probity, public accountability, and auditor competence on the quality of government internal audits. Additionally, the study examines the role of rewards as a moderating variable within the context of the BPK RI North Sumatra Representative. The study utilized a saturated sampling technique to select 48 participants, and data collection was conducted via questionnaires. Statistical analysis was performed using the MRA (Multiple Linear Regression Analysis) method with SPSS version 25. The findings from partial statistical tests reveal that neither internal supervision nor audit probity significantly impacts the quality of government internal audits. Conversely, public accountability and auditor competence demonstrate a positive and significant relationship with internal audit quality. When analyzed collectively, internal supervision, audit probity, public accountability, and auditor competence collectively contribute positively to the quality of internal audits. However, rewards do not serve as a moderating factor for the relationships between internal supervision, audit probity, public accountability, and audit quality. In conclusion, this study provides critical insights into the determinants of government internal audit quality. The results underscore the vital role of public accountability and auditor competence in enhancing the effectiveness of internal audits. Nonetheless, greater efforts are required to strengthen internal supervision and audit probity to achieve overall improvements in audit quality.